STUDI POTENSI TAMPUNGAN HULU DPS SUNGAI SAMPEAN UNTUK PENGENDALIAN BANJIR DAN PENYEDIAAN AIR BERSIH - Umboro Lasminto (Purifikasi, 2009)
Floods in Kabupaten Situbondo and Bondowoso were caused by overtopping of Sampean River. This paper discusses a study on control of Sampean River by utilizing the potential upstream reservoir. The upper reservoir was used to receive part of the rain water, so that the discharge to the main river could be reduced and the stored water can be used as water resource and water conservation. The discharge through the Sampean River was much greater than the flow capacity. The results of the survey and analysis indicated that eleven locations were potential for reservoir. These locations were dam sized sites in the main river, and ten locations in the tributaries of small dam size. The Tasnan dam had a potential water storage capacity up to 3.1 million m3, whereas the small dams were of 100,000 to 500,000 m3. By analyzing the 50-year raining return period, the Tasnan dam potentially reduced the floodi as much as 99.5 m3/s. The small dams of Walidono 1, Walidono 2, and Cangkring can reduce the discharge up to 5.9, 3.9, and 2.2 m3/s, respectively. Meanwhile, the small dams of Mandiro, Selolembu, Pandak, Pakis, Gubri 1, Gubri 2, and Cabang only had very small potential capacities in reducing the flood.